LEXICAL AND SYNTACTIC FEATURES OF THE EXPRESSION OF REPROACH (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Reproach is a commonly observed mode of communication in human interactions. Whenever an individual feel dissatisfied or let down by someone else's actions, they tend to convey their disapproval through reproach. This can manifest in various ways, such as direct criticism, subtle insinuations, or indirect remarks. The present article aims to delve into the lexical and syntactic aspects of reproach, encompassing the words and structures frequently employed to convey disapproval.